Senescent declines in elite tennis players are similar across the sexes - Sutter, A.; Barton, S.; Dev Sharma, M.; Basellini, U.; Hosken, D. J.; Archer, C. R. (Behavioral Ecology, 2018)
Aging is characterized by rising mortality, declining fertility and declines in physiological function with age (functional senescence). Sex differences in the tempo and severity of survival and fertility declines are widespread, but it is less clear how often and how much trajectories of functional senescence diverge between the sexes. We tested how physiological function changed with age in male and female elite tennis players using first-serve speed (power) and first-serve accuracy as performance measures. We found absolute differences between the sexes with men serving faster, but less accurately than women. Both power and accuracy showed senescent declines but these began earlier for power. There were signals of trait-compensation, where players with pronounced power declines showed relative increases in accuracy, which might partially buffer against power deterioration. However, there were no sex differences in how either trait changed with age, contrasting with other sports. Sex differences in functional senescence are probably shaped by interactions between natural and sexual selection, the proximate costs of trait expression and a trait`s genetic architecture, and so are highly trait-specific. We discuss the strengths and potential pitfalls of using data from elite athletes to disentangle these complex interactions.